Midkine is a tumor cell survival factor that displays metastatic and therapeutic resistance functions in uveal melanoma - Karg, Margarete; John, Lukas; Refaian, Narin; Büttner, Christian; Rottmar, Tanja; Sommer, Jonas; Bock, Barbara; Resheq, Yazid; Ksander, Bruce; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Midkine Promotes Metastasis and Therapeutic Resistance via mTOR/RPS6 in Uveal Melanoma. - Karg, Margarete; John, Lukas; Refaian, Nasrin; Büttner, Christian; Rottmar, Tanja; Sommer, Jonas; Bock, Barbara; Resheq, Yazid; Ksander, Bruce R.; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Molecular Cancer Research, 2022)
Uveal melanoma is a rare form of melanoma that originates in the eye, exerts widespread therapeutic resistance, and displays an inherent propensity for hepatic metastases. Because metastatic disease is characterized by poor survival, there is an unmet clinical need to identify new therapeutic targets in uveal melanoma. Here, we show that the pleiotropic cytokine midkine is expressed in uveal melanoma. Midkine expression in primary uveal melanoma significantly correlates with poor survival and is elevated in patients that develop metastatic disease. Monosomy 3 and histopathologic staging parameters are associated with midkine expression. In addition, we demonstrate that midkine promotes survival, migration across a barrier of hepatic sinusoid endothelial cells and resistance to AKT/mTOR inhibition. Furthermore, midkine is secreted and mediates mTOR activation by maintaining phosphorylation of the mTOR target RPS6 in uveal melanoma cells. Therefore, midkine is identified as a uveal melanoma cell survival factor that drives metastasis and therapeutic resistance, and could be exploited as a biomarker as well as a new therapeutic target. IMPLICATIONS: Midkine is identified as a survival factor that drives liver metastasis and therapeutic resistance in melanoma of the eye.
EVALuna2:503899